The accuracy of PJOK in Service Teachers Designing Assesment: A Case Study of Long Jump - Achmad Nuryadi; Bayu Akbar Harmono; Muhammad Wahyono; Arnaz Anggoro Saputro (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
One branch of sportis athletics and it was explained that getting maximum results in this sport is of course influenced by one's physical abilities. Purpose: to measure the accuracy of the psychomotor assessment instrument developed by the PJOK teacher on long jump material. Methods: Two teachers subject participated in this study. Documentation method used in this study then were analyzed used four indicators. Results and discussioin: The assessment instrument developed by the subject is still not sufficient to assess students' long jump abilities. Each item needs to be specified further to make it easier for the observer. Conclusion and Implications: The developed instrument is not appropriate so it needs for the further. It is necessary to have workshop activities to train PJOK teachers to develop assessment instruments. Limitation and recommendation: This study is only limited to the development of long jump psychomotor assessment. So, it is necessary to further develop psychomotor instruments in other sports